Sojourn or Stay: International Academics and Researchers in Australia - Welch, Anthony (International Higher Education, 2022)
Australian higher education is highly diverse, with numbers of researchers and academics from Asia rising the most, especially in recent decades. The knowledge diasporas of China and India, two major sources, contribute to teaching and research but also help to build bridges with their homelands and international scientific networks—contributions that are not always fully valued. US–China tensions and COVID-induced travel restrictions have interfered with the contributions of many international staff.